EMPOWERING EDUCATION THROUGH AI: POTENTIAL BENEFITS AND FUTURE IMPLICATIONS FOR INSTRUCTIONAL PEDAGOGY - Alashwal, May (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study explores the transformative potential of Artificial Intelligence (AI) in education. AI-powered systems offer a paradigm shift from traditional methods, fostering personalized learning experiences. The paper examines various AI applications including intelligent tutoring systems, virtual reality environments, and advanced data analysis. Machine learning algorithms personalize learning journeys by analyzing student data and preferences. Learner models track progress and adapt instruction based on strengths and weaknesses. The research identifies potential benefits such as improved access to education, enhanced student engagement, and streamlined administrative tasks. Additionally, the paper explores the future implications of AI in education, including adaptive assessments, virtual teaching assistants, and increased parental involvement. Recommendations for further research emphasize exploring AI's role in instructional pedagogy, integrating AI concepts into the curriculum, and providing hands-on learning opportunities through AI projects. Overall, the study highlights AI's potential to revolutionize education by creating a more individualized and effective learning environment for all students.